Placental hyperinflation and the risk of adverse perinatal outcome. (2nd September 2013) - Porat, S.; Fitzgerald, B.; Wright, E.; Keating, S.; Kingdom, J. C. P.
ABSTRACT Objectives To determine the pathological basis and clinical associations of excessively thick placentae observed at second‐trimester ultrasound examination. Methods In a retrospective cohort of 19 singleton high‐risk second‐trimester pregnancies noted to have a placental length‐to‐maximum thickness ratio ≤ 2.0, maximum sonographic placental thickness was correlated with clinical outcome, maximum placental thickness after delivery and placental pathological findings. Results were compared with those of an intermediate group of 21 high‐risk pregnancies with normal placental dimensions and a control group of 18 low‐risk pregnancies also with normal placental dimensions. Increased maximum placental thickness (> 28 mm) and abnormal placental deflation following delivery (pathology − sonography difference in maximum placental thickness < −2 mm) were defined by the upper and lower quartile values, respectively, in the control group. Results The study group exhibited significantly more adverse outcomes and gross pathological placental features compared with both intermediate and control groups. Despite increased sonographic maximum placental thickness in the study group (median, 55 (range, 40–75) mm compared with both the intermediate group (median, 27 (range, 22–41) mm, P < 0.0001) and the control group (median 26 (range, 23–36) mm, P < 0.0001)), all three groups had similar maximal placental thickness following delivery (study group: median, 24 (range, 10–50) mm vs intermediate group: median, 27 (range, 15–40) mm, P = 0.82 and vs control group: median, 28.5 (range, 18–44), P = 0.42). Pathology − sonography difference in maximum placental thickness in the study group (median, –30 (range, –42 to 0) mm) was significantly greater than that in either the intermediate (median, –2 (range, –11 to 9) mm, P < 0.0001) or the control (median, 1.5 (range, –10 to 18) mm, P < 0.0001) group and was significantly associated with abnormal development of the gas‐exchanging placental villi (distal villous hypoplasia) (P = 0.0001). Conclusions Increased second‐trimester sonographic maximum placental thickness represents a pathological finding associated with severe adverse perinatal outcome. This observation is due to overinflation of the intervillous space by maternal blood rather than to adaptive formation of functional placental tissue. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.